RISK ASSESSMENT OF A SUICIDE IN RELATION TO A PERSONALITY STRUCTURE IN PATIENTS WITH DEPRESSION - Sojević, Milica; Purić, Nemanja; Dunjić-Kostić, Bojana (Medicinski podmladak, 2017)
Introduction: The issue of suicidal risk ,and suicide in general, represents one of the biggest challenges in psychiatric evaluation. This issue is covered by an extensive scientific work with the purpose of creating the most precise evaluation of suicide and suicide risk. The Aim: The main goal of this research is to validate psychopatological constructs of a personality isolated by MMPI and HAMD in relation with measured suicidal rate among the subjects in question. Also, goal of this research is to explore possible connecitons beetween standard clinical and sociodemographic variables with rate of suicidality. Materials and methods: The sample group consists of patients that are based on the stationary ward of a psychiatric clinic, diagnosed with F32 and F33. All the data was collected by interview, questionnaire and official medical documentation. The prediction variables are presented by the score on MMPI-202 and HAM-D, and standard clinical and sociodemographic variables. Criteria variables represent the score on SBQ-R, as a measure of suicidal tendencies, and a category variable which marks the presence of suicide attempts in the past. During the data analysis, the following methods were used: descriptive statistics, bivariate correlation, regression analysis, comparisment of arithmetic mean and canonical discriminant analysis. Results: The research showed a positive and significant correlation between suicidal tendencies and the scales of: depression, paranoia, schizophrenia, psychoastenia (p